Recent advances in magnetic carbon nanotubes: synthesis, challenges and highlighted applications. Issue 44 (20th October 2021) - Guo, Jiabei; Jiang, Hui; Teng, Yan; Xiong, Yue; Chen, Zhuhui; You, Linjun; Xiao, Deli
Abstract : Magnetic carbon nanotubes (MCNTs), consisting of carbon nanotubes (CNTs) and magnetic nanoparticles (MNPs), have enormous exploration and application potentials due to their superior physical and chemical properties, such as unique magnetism and high enrichment performance. Abstract : Magnetic carbon nanotubes (MCNTs), consisting of carbon nanotubes (CNTs) and magnetic nanoparticles (MNPs), have enormous exploration and application potentials due to their superior physical and chemical properties, such as unique magnetism and high enrichment performance. This review concentrates on the rapid advances in the synthesis and application of magnetic carbon nanotubes. Great progress has been made in the preparation of MCNTs by developing methods including chemical vapor deposition, pyrolysis procedure, sol–gel process, template-based synthesis, filling process and hydrothermal/solvothermal method. Various applications of MCNTs as a mediator of the adsorbent in magnetic solid-phase extraction, sensors, antibacterial agents, and imaging system contrast agents, and in drug delivery and catalysis are discussed. In order to overcome the drawbacks of MCNTs, such as sidewall damage, lack of convincing quantitative characterization methods, toxicity and environmental impact, and deficiency of extraction performance, researchers proposed some solutions in recent years. We systematically review the latest advances in MCNTs and discuss the direction of future development.